MOOCs for Reskilling and Upskilling: A Perspective of Employees’ Acceptance - Alasmari, Talal (International Journal of Multi Discipline Science (IJ-MDS), 2024)
MOOCs have transformed professional development, yet businesses lack data on employee adoption, hindering the optimization of digital learning initiatives. This study investigated factors influencing Saudi Arabian employees' behavioural intentions and MOOC usage across sectors. Utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) model, we examined how performance expectancy, effort expectancy, social influence, facilitating conditions, and behavioural intention affect MOOC adoption. Online surveys were distributed to 1036 participants from diverse industries using snowball sampling. This research employed the Partial-Least-Square-Structural-Equation-Modelling (P-L-S-S-E-M) approach in two phases. Results indicated that performance expectancy, effort expectancy, and facilitating conditions significantly impact employees' MOOC intentions and usage, while social influence does not. Years of experience and sector moderate these relationships. This research provided empirical evidence and actionable insights for corporations investing in MOOCs, suggesting strategies to address employee needs across sectors and experience levels, foster a supportive organizational culture, and incentivize MOOC usage for professional development and reskilling, particularly among more experienced employees.